Green satisfaction as a bridge to improved green customer loyalty - Rahayu, Sri; Setiyawami, Setiyawami; Marjuki, Marjuki; Fitriani, Silfi; Rahmawati, Hanafi Hajar; Anjani, Dina Nursya (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2025)
This study aims to examine the impact of green product quality, green brand image, green satisfaction, and green trust on green consumer loyalty. It also investigates the mediating role of green satisfaction in the relationship between green product quality, brand image, trust, and consumer loyalty. Employing a quantitative approach, the research focuses on consumers of The Body Shop beauty products in D.I. Yogyakarta. Primary data were collected through questionnaires from 160 respondents and analyzed using SEM SmartPLS. Findings reveal that a green brand image has a significant influence on both green satisfaction and green consumer loyalty. Green satisfaction likewise has a significant positive effect on green consumer loyalty. Additionally, green trust has a significant impact on green satisfaction. However, the effects of green trust on consumer loyalty, as well as green product quality on both satisfaction and loyalty, were found to be insignificant. Further analysis reveals that green satisfaction mediates the relationships between green brand image and consumer loyalty, as well as between green trust and consumer loyalty. Conversely, green satisfaction does not mediate the effect of green product quality on consumer loyalty. These results suggest that while brand image and trust enhance loyalty through satisfaction, product quality alone does not have a significant mediated impact on loyalty